Motivations and benefits of ISO system implementation in transportation-related companies: marketing aspect of ISO - Ivanauskienė, Laima; Urbonavičius, Sigitas (Transport, 2003)
The paper analyses the effects of ISO system implementation and certification. It separately reviews motivations to implement ISO system and benefits after the system implementation. The authors analyse motivations and benefits that are internal (managerial) and external (mainly – marketing type). The analysis is performed on the basis of the survey of Lithuanian companies, comparing findings with similar research in other countries. Industry (sectorial) specifics is analysed on the basis of transportation-related companies group.First Published Online: 19 Dec 2011